Biosynthesis, Characterization and Antibacterial effect of Zno Nanoparticles Synthesized by Lactobacillus Spp - Jehan Abdul Sattar Salman (Journal of Global Pharma Technology, 2018)
Biosynthesis of Zinc oxide (ZnO) nanoparticles using a probiotics bacteria Lactobacillus spp. which isolated from different sources was studied. The formation of ZnO nanoparticles was checked using X-ray diffraction (XRD) technique, Atomic Force Microscopy (AFM), Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopic (SEM) and Energy-dispersive X-ray analysis (EDX) spectra. The characterization results showed that the biosynthesized nanoparticles are hexagonal ZnO crystal structure, spherically shaped with a diameter of about (30.3 - 38) nm. The antibacterial effect of the synthesized ZnO nanoparticles was determined through the minimum inhibitory concentration (MIC) against pathogenic bacteria isolated from skin infections included Pseudomonas aeruginosa, Acinetobacter baumanii, Klebsiella pneumonia , and Staphylococcus aureus. The synthesized ZnO nanoparticles were effective against all the tested pathogenic bacteria at different degrees. The best effect has been shown against A. baumannii with MIC recorded at 12.5mg/ml, but the lowest effect has been recorded on P. aeruginosa(50mg/ml).Keywords: Biosynthesis, ZnO nanoparticles, Lactobacillus spp., Antibacterial activity, Skin infections.